PRESERVATION OF INDIGENOUS KNOWLEDGE OF MINANGKABAU KAIN SONGKET AS AN EFFORT TO PRESERVE CULTURE - Miftahunnisa' Igiriza; Rahmat Alifin Valentino; Gunawan Wiradharma; Rosiana Nurwa Indah; Salaisyah Amalia Yusuf (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
Minangkabau songket not only functions as traditional clothing but also as a container of local knowledge that represents symbolic meaning, philosophical values, and the collective outlook on life of the Minangkabau people. This study explores indigenous knowledge in songket motifs and the preservation strategies of the Adityawarman Museum. A qualitative method was applied using two approaches: Peirce's semiotics to analyze indigenous knowledge and a case study for preservation at the museum. Data were collected through interviews, non-participatory observation, and documentation, with museum curators purposively selected as informants. Data were analyzed using the Miles & Huberman interactive model and interpreted through Peirce's semiotics. The results show that the motifs on Minangkabau songket cloth, including the Pucuak Rabuang, Itiak Pulang Patang, Kaluak Paku, Saluak Laka, and Barantai motifs, reflect philosophical values, collective identity, and ethics embedded in Minangkabau culture. The process of preserving local wisdom carried out by the Adityawarman Museum of West Sumatra through six integrated stages of introduction, validation, documentation, storage, transfer, and dissemination, with the support of community participation and the use of digital technology. The conclusion in this study shows that the traditional knowledge of Minangkabau songket represents Minangkabau cultural knowledge that can be passed down from generation to generation through the meaning contained in each motif and the Adityawarman Museum plays an important role in preserving the original knowledge of Minangkabau songket. Theoretical contributions include expanding cultural semiotics and strengthening perspectives on indigenous knowledge preservation, offering novelty in the study of the relationship between symbols, culture, and local knowledge preservation.